PARTY SYSTEM INSTITUTIONALIZATION AND THE PROSPECT OF DEMOCRATIC CONSOLIDATION IN ETHIOPIA - Abeje, Alefe (European Scientific Journal, ESJ, 2013)
The principal democratic institutions in democracy are political parties. Party law plays a crucial role in institutionalizing multi-party politics. Institutionalization of a party system is vital for the success of democratic system. Unfortunately, several writers show a bleak picture concerning the institutionalization of African political system in general and the party system in particular (Lindberg, 2007; Bogaards, 2003). Given multiparty politics is a late comer in Ethiopia, this problem is perhaps more direr in Ethiopia. Observation of their structure, social base, resources, procedure of internal decision-making, and the like clearly show the weak level of institutionalization as assumed by democratic theory. Thus, they are less likely to fulfill their democratic functions in democracy. Given these problems, strict implementation of the regulatory regimes, especially in the areas of internal democracy and transparency of financial management, is an important in step towards institutionalization. But, there should be a delicate balance as heavy-handed regulation at early stage of party development may become counterproductive (Randall, 2008: 256).